PENGARUH TWIST ANGLE BLADE TURBIN SAVONIUS BERPENGARAH ALIRAN APLIKASI PADA TURBIN AIR - Rendi Rendi; Abdurrahim Sidiq (Universitas Lambung Mangkurat, 2018)
Water turbine is one of the mechanical equipment that functions to generateenergy into mechanical energy. There are types of water turbines one of which isthe Savonius water turbine. Savonius water turbines have the advantage of otherturbines, namely installation in rivers that do not damage the environment, areable to work and do not require special maintenance as well as providingweaknesses that can affect the positive force and the negative force on the rotor isstill small. This turbine has never been widespread. To make this turbine it ispossible to conduct research to improve its performance, especially in the turbinerotor. In these words we will try the rattan turbine by varying the blade's turningangle from 00, 30o, 60o, 90o and 120o and adding ½ and ¼ opening flow guides.Based on the results of the research that we have done, we can say the differencein blade angle and flow guide to turbine performance. The variation of twist angleand flow controller that provides the most appropriate turbine performance is a90o swivel with turbine flow guide openings ¼. At the swivel angle 120o the waveguide is not as wide.